(untitled) (Research, Society and Development, 2020)
As the environmental issues become more pressing, Municipal Environmental Councils started to spread in Brazil over the last 20 years. This non-mandatory consultative and normative body is composed of volunteers from both public and private sector, aiming to discuss and recommend solutions that affect the local environment. Leadership of this council is expected to work as mediators between competitive perspectives. The present paper aims to analyze situational leadership in the Municipal Environmental Council of the city of Santa Maria, in the south of Brazil. Literature in situational leadership and environmental leadership was used to base our discussion. Primary data was collected through both structured forms and semi-structured interviews with two Coordinators of the Council. Results indicate a high level of maturity of the teams, with leaders acting mostly as mediators, with a high level of delegation. As council members tend to be interested and connected to the environmental agenda, a high level of motivation and capabilities is found, creating more mature teams and enabling a more “hands-off” approach from the leader figure.